Commissioning of a Highly Customized 1010 nm, ns-Pulsed, Yb-Doped Fiber Amplifier for On-Demand Single-Photon Generation - Mausezahl, Max; Christaller, Florian; De Vries, Oliver; Plotner, Marco; Zhang, Hao; Belz, Annika; Heinrich, Benjamin; Walbaum, Till; Schreiber, Thomas; Tunnermann, Andreas; Kubler, Harald; Low, Robert; et al. (2021 Conference on Lasers and Electro-Optics, CLEO 2021 - Proceedings, 2021)
Parametric single-photon generation is a key technology for quantum-optical applications. Here we report on the development and commissioning of a highly specialized 1010 nm fiber amplifier for such a novel parametric single-photon source.
CRIS-Team Scopus Importer:2023-04-20